Kesalahpahaman Makna Gugatan Perwakilan Kelompokdan Legal Standing di Indonesia - Machsun Tabroni (Fakultas Hukum Universitas Islam Indonesia, 2004)
A long side conventional civil suits, the development of the civil law of procedure_ hasled to the emergence of class action and legal standing. A class action is filed by one or more –persons in the irown interests, butal soon be half of and in the interests ofa large group of people; where as legal standing is merelyan